2002
DOI: 10.3189/172756402781817987
|View full text |Cite
|
Sign up to set email alerts
|

Spectral snow-reflectance models for grain-size and liquid-water fraction in melting snow for the solar-reflected spectrum

Abstract: Two spectral snow-reflectance models that account for the effects of grain-size and liquid-water fraction are described and initial validation results presented. The models are based upon the spectral complex refractive index of liquid water and ice in the region from 400 to 2500 nm. Mie scattering calculations are used to specify the essential optical properties of snow in the models. Two approaches are explored to model the effect of liquid water in the snow. The first accounts for the liquid water as separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 12 publications
1
74
0
Order By: Relevance
“…Otherwise, it could be related to the presence of meltwater increasing the absorption of solar radiation during the melting season, as observed from airborne hyperspectral reflectance data in other glaciers of the European Alps (Naegeli et al, 2015). Spectra of bare ice exhibit low reflectance, showing an enhanced absorption around 1030 nm, slightly shifted to lower wavelengths (Dumont et al, 2017;Green et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Otherwise, it could be related to the presence of meltwater increasing the absorption of solar radiation during the melting season, as observed from airborne hyperspectral reflectance data in other glaciers of the European Alps (Naegeli et al, 2015). Spectra of bare ice exhibit low reflectance, showing an enhanced absorption around 1030 nm, slightly shifted to lower wavelengths (Dumont et al, 2017;Green et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…How- Figure 14. Radiative forcing of snow impurities with respect to terrain elevation (left panels) and aspect (right panels) in the Sierra Nevada in spring 2009. ever, Green et al (2002) showed in a controlled field experiment that grain size retrievals leveraging the 1.03 µm ice absorption feature were invariant from dry snow to melting snow conditions. Likewise, grain size retrievals from AVIRIS data across larger regions in the Sierra Nevada remained largely stable under change from dry to melting conditions (Dozier et al, 2009).…”
Section: Uncertainty and Error Analysismentioning
confidence: 98%
“…1c; Nolin and Dozier, 2000;Painter et al, 2007). However, this may not hold for large grain radii or high impurity concentrations, and the absorption feature can be shifted to shorter wavelengths by liquid water (Green et al, 2002(Green et al, , 2006Gallet et al, 2014). The same may be true for NIR (0.7-1.3 µm) photographic methods (Yamaguchi et al, 2014).…”
Section: Characterising Snow or Ice Optical Characteristicsmentioning
confidence: 99%